Avaliação do tratamento da halitose com terapia fotodinâmica em indivíduos idosos portadores de próteses totais: estudo randomizado e controlado - Vale, Kátia Llanos do (2019)
Halitosis refers to an unpleasant odor that emanates from the oral cavity (bad breath). The origin of halitosis is mainly correlated to the release of hydrogen sulfide gas (H2S) from the metabolism of gram negative bacteria lodged in the tongue dorsum. There is a correlation between aging and increased halitosis. Photodynamic therapy (PDT) has been used in the tretament of halitosis, but there are no reports of its effects for this age group. This study compared the effect of PDT and tongue scraping (standard treatment) in elderly individuals with complete denture diagnosed with halitosis (H2S >112 ppb). Subjects were divided into groups: G1- treatment with tongue scraping (n = 20); G2- treatment with PDT (n = 20). Halimetry was performed immediately after treatments by gas chromatography. In cases that halitosis persisted, denture and mucosal cleaning was performed. The halimetry was repeated after seven days. Oral health-related quality of life was assessed using the Oral Health Impact Profile (OHIP-14) questionnaire at the first visit and after seven days. Immediately after treatment, the average concentration H2S gas concentration was lowered (p = 0.003) in the PDT group (698.7ppb to 18.5 ppb) than in the Scraping group (736.7 ppb to 185.3 ppb). After 1 week, the mean H2S concentration in the Scraping group increased to 218.2 ppb and the PDT group to 39 ppb (p <0.000). No differences were found between the two groups and also between the two-time groups for the total scores and domains of the OHIP-14 questionnaire. This study showed that both treatments were able to decrease H2S gas concentration but only the treatment with PDT was able to reduce halitosis to socially unnoticeable levels. In addition, this normal breath condition was remained for 7 days in the PDT- treated group.